Leber's hereditary optic neuropathy: correlations between mitochondrial genotype and visual outcome. Issue 4 (April 1994) - Oostra, R J; Bolhuis, P A; Wijburg, F A; Zorn-Ende, G; Bleeker-Wagemakers, E M
Abstract : Leber's hereditary optic neuropathy (LHON) is a maternally inherited disease associated with mitochondrial DNA (mtDNA) mutations. We describe the distribution of seven different mtDNA mutations and the clinical findings in 334 LHON patients belonging to 29 families. Mutations described only in LHON at nucleotide positions 11778, 3460, and 14484 were found in 15, two, and nine families respectively. In three families none of these mutations was found. Mutations described in LHON but also in controls at nucleotide positions 15257, 13708, 4917, and 4216 were found in one, 10, three and 12 families respectively. Combinations of mtDNA mutations were found in most families. The patient population mainly consisted of 79.2% to 89.5% males except for one family with only 10 of 17 patients being males (58.9%, p approximately 0.036). In 11 families only the 11778 mutation was found; in this group (WX) the affected males had a mean age of onset of 29.2 years and a mean visual outcome of 0.113. In seven families the 14484, 13708, and 4216 mutations were found; in this group (MA) the affected males had a mean age of onset of 22.0 years and a mean visual outcome of 0.442. In two families no mutation was found at all; in this group (YX) the affected males had a mean age of onset of 18.9 years and a mean visual outcome of 0.167. The mean age of onset in the WX group is significantly higher than in the MA group (p < or = 0.001) and in the YX group (p approximately 0.01). The mean visual outcome in the MA group is significantly better than in the WX group (p </= 0.001) and the YX group (p = 0.05). No significant clinical differences were found between families exhibiting only the 11778 mutation and those with additional mutations at np 13708, 4917, or 4216, suggesting that these mutations are of little phenotypic importance. Other mutations were present in relatively small numbers of patients. These results show that the clinical severity is dependent on the mitochondrial genotype.